88 Routine Post-Operative Troponin Screening for Myocardial Injury after Noncardiac Surgery (MINS) Events – A Single Centre Experience. (3rd June 2016) - Jackson, Matthew; Cunningham, Nicola; Hammond, Mark; Austin, David; Swanson, Neil; Belder, Mark de; Stewart, Michael
Abstract : Introduction: The VISION study demonstrated an association between 30-day mortality after surgery and raised post-operative troponin levels. 1 Subsequently, diagnostic criteria for 'ischaemic' MINS were established excluding non-ischaemic aetiology. 2 We evaluated our initial experiences with post-operative troponin monitoring, to look in-depth at patients who suffer MINS events. Methods: Pre- and post-operative high-sensitive troponins were checked on all elective and emergency surgical patients over 45 years of age with an inpatient stay of more than 2 days between August 2014 and June 2015. A MINS event was defined as in the VISION (1) study as any positive post-operative troponin. Thirty-day mortality after surgery was determined via HES data. Notes, pathology reports and discharge letters were reviewed for evidence of sepsis, prolonged tachycardia, multi-organ failure or significant bleeding (Hb loss of >5 g/l and/or total Hb <8 g/dl). Events were classified as 'non MINS', 'unexplained MINS' or 'secondary MINS' due to one of these provoking factors. Cox regression analysis was performed to assess association between variables. Results: 388 patients were studied. 196 were male with a mean age of 69 years (range 45–95). 132 (34%) were emergency admissions. 245 (63.1%) had normal post-operative troponins (i.e. non MINS), with 81 (20.9%), 49 (12.6%) and 13 (3.4%) recording troponin levels of 17–50, 51–1000 and more than 1000 respectively. 21 of the positive post-op values represented a downward trend from pre-op tests, with a further 17 positive pre-op values falling into the normal range post-operatively. The 30 day mortality rate was 2.8% compared to 1.9% in VISION. Of the 11 deaths, 10 (90.9%) were emergency admissions. Two (18.2%) deaths occurred in patients exhibiting a downward trend in troponin and 3 (27.3%) had a normal post-operative troponin (i.e. did not suffer a MINS event). Discussion: A raised post-operative troponin was associated with poor prognosis as suggested in the VISION study (p = 0.022 HR 0.213 [0.057–0.803]). Sepsis was also associated with a poor prognosis (p < 0.001 HR 0.08 [0.021–0.305]) as is emergency admission for surgery (p = 0.004 HR 0.05 [CI 0.006–0.392]). However, there was no mortality from 'ischaemic' MINS events (unexplained events and events secondary to tachycardia and bleeding). Whether MINS events are a separate clinical entity related to unstable or significant coronary disease or a reflection of other poor prognostic factors remains unclear. Further studies assessing coronary anatomy may be useful in delineating this further. References: Devereaux PJ, Chan MT, Alonso-Coello P, et al . Association between Post-operative Troponin Levels and 30-Day Mortality among Patients undergoing Noncardiac Surgery. JAMA . 2012;307(21) Myocardial Injury After Noncardiac Surgery. VISION Study Investigators.  Anaesthesiology, 2014;120: 564-–78